La innovación curricular orientada a competencias en la Facultad de Medicina de la Universidad de Chile - Castillo N., Manuel (Revista Hospital Clínico Universidad de Chile, 2014)
This article tries to give an overview of the educational changes that have been taking place in the Faculty of Medicine, University of Chile, known as “The Process of Curricular Innovation” which is based on a competence-oriented desirable profile for its graduates. This change seeks to generate a higher quality of teaching processes considering the current needs of our society. The concepts of competences and curriculum design are reviewed here for a better understanding of the innovation process.